2022
DOI: 10.48550/arxiv.2203.12641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Starry Byte -- proton beam measurements of single event upsets and other radiation effects in ABCStar ASIC Versions 0 and 1 for the ITk strip tracker

M. J. Basso,
J. Fernandez-Tejero,
B. J. Gallop
et al.

Abstract: Single Event Effects (SEEs) -predominately bit-flips in electronics caused by particle interactions -are a major concern for ASICs operated in high radiation environments such as ABCStar ASICs, which are designed to be used in the future ATLAS ITk strip tracker. The chip design is therefore optimised to protect it from SEEs by implementing triplication techniques such as Triple Modular Redundancy (TMR).In order to verify the radiation protection mechanisms of the chip design, the cross-section for Single Event… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…To ensure the ITk detector will meet its operational requirements in the radiation environment of the HL-LHC, the performance of strip modules and their electronics has been evaluated in numerous beam tests using electrons [16,17] as well as protons and heavy ions [18][19][20]. From measurements performed with monochromatic photon beams [21,22], it has been observed that high fluxes of photons incident on a single strip -O (1) photons/25 ns -cause the corresponding hit efficiency 𝜀 to significantly deviate from the expected "S-curve":…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the ITk detector will meet its operational requirements in the radiation environment of the HL-LHC, the performance of strip modules and their electronics has been evaluated in numerous beam tests using electrons [16,17] as well as protons and heavy ions [18][19][20]. From measurements performed with monochromatic photon beams [21,22], it has been observed that high fluxes of photons incident on a single strip -O (1) photons/25 ns -cause the corresponding hit efficiency 𝜀 to significantly deviate from the expected "S-curve":…”
Section: Introductionmentioning
confidence: 99%